2016
DOI: 10.1371/journal.pone.0164503
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration Networks in Applied Conservation Projects across Europe

Abstract: The main funding instrument for implementing EU policies on nature conservation and supporting environmental and climate action is the LIFE Nature programme, established by the European Commission in 1992. LIFE Nature projects (>1400 awarded) are applied conservation projects in which partnerships between institutions are critical for successful conservation outcomes, yet little is known about the structure of collaborative networks within and between EU countries. The aim of our study is to understand the nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 48 publications
(66 reference statements)
2
34
0
Order By: Relevance
“…As brown bears may use multiple GMUs annually or during a single season, a regional approach to monitoring based on remote cameras and track counts (Popescu et al 2017) or non-invasive DNA techniques (Proctor et al 2010) is likely to yield better results and will require coordination between multiple adjacent GMUs. Additionally, conservation initiatives should cover large areas, which seems to be difficult in Romania given the tendency of conservationists to work at a local scale (Nita et al 2016). This study provides important information for future brown bear research and conservation, such as habitat selection studies, habitat connectivity and population estimates for Romania's brown bear population.…”
Section: Discussionmentioning
confidence: 95%
“…As brown bears may use multiple GMUs annually or during a single season, a regional approach to monitoring based on remote cameras and track counts (Popescu et al 2017) or non-invasive DNA techniques (Proctor et al 2010) is likely to yield better results and will require coordination between multiple adjacent GMUs. Additionally, conservation initiatives should cover large areas, which seems to be difficult in Romania given the tendency of conservationists to work at a local scale (Nita et al 2016). This study provides important information for future brown bear research and conservation, such as habitat selection studies, habitat connectivity and population estimates for Romania's brown bear population.…”
Section: Discussionmentioning
confidence: 95%
“…For example, Holmes-Watts and Watts (2008) found that while policy and even practice of participatory forest management in South Africa emphasizes community participation, this is largely passive, subject to a "tick-box" mentality amongst practitioners and lacks the forms of devolution necessary to sustain community support. Such challenges are experienced in a range of other jurisdictions as well, including Europe (Kluvánková-Oravská et al, 2009;Nita et al, 2016). It is imperative that conservation interventions are framed around institutionalized processes that encourage the coproduction of knowledge and solutions in which meaningful partnerships are formed.…”
Section: Multilevel Network and Collaborative Relationshipsmentioning
confidence: 99%
“…) and other large carnivores (lynx [ Lynx lynx ], wolf [ Canis lupus ]) was banned by the Ministry of Environment in part because of the weak scientific basis for setting bear hunting quotas (Popescu et al. ), the perceived influence of certain economic interests in determining annual quotas (i.e., trophy hunting in the case of bears), and intense public campaigns seeking a ban on hunting of protected large carnivores (WWF ). Because this policy change was implemented without due consideration of other measures to prevent human–large carnivore conflict and efficient compensation, some stakeholders responded by successfully requesting that the government reinstate hunting.…”
Section: Human–large Carnivore Conflict In Romania After a Hunting Banmentioning
confidence: 99%
“…Academia does not always have a direct and facilitative role in their formation, but it can contribute to their functioning through training, knowledge sharing, critical thinking and analysis, and innovation and monitoring (e.g., Nita et al. ; Rozylowicz et al. ).…”
Section: Lessons For Fostering Human–large Carnivore Coexistence In Hdlsmentioning
confidence: 99%
See 1 more Smart Citation